SISTEM KOREKSI POSTUR DUDUK DENGAN BETASPC BERBASIS ARDUINO DUEMILANOVE - Mukti Budiarto; Andri Ahmad Gozali; Hidayaturrohman Hidayaturrohman (CCIT Journal, 2016)
BetaSPC is a technology that uses a microcontroller (Arduino Duemillanove) as processors and sensors (infrared) which is based on the amount of light reflected on a clothes stretched (when the bent body position). With the technology used in BetaSPC allows one to determine the proper posture when sitting at a computer or laptop and improve posture during sitting. When someone is in front of the laptop or computer by sitting in an upright posture, the posture shoulder (shoulder) on the back will change clothes behind, just below the shoulder blade position becomes meragang. If someone sitting at a computer or laptop to a sitting position in a bent posture then clothes (clothes) behind, just below the shoulder blade will be stretched (tight). Then, stretch clothes that will activate the buzzer (sound and vibrate) to provide feedback to the user about the current posture stretch shirt (hunchback) so as to commemorate and improve the position of his body correctly (perpendicular) when using a computer or laptop.